(untitled) (Journal of Pathology of Nepal, 2020)
Squamous cell carcinoma and adenocarcinoma are the most common histological types of cervical cancer. The co-existence of two histological types is rare. Here we report a case of a 65-year-old woman with a complaint of postmenopausal bleeding and a history of foul-smelling discharge per vagina for 8 months. On examination cervix flared up with growth, bled on touch, parametrium was involved and adherent anteriorly with bladder & posteriorly with the rectum. Cervical biopsy revealed small cell carcinoma coexisting with Adenocarcinoma. Later it was confirmed by immunohistochemistry.